Fields of predicativeness and possessiveness in the Kazakh language. (Eurasian Journal of Philology Science and Education, 2015)
The object of the given article is grammatical categories of predicate and possessiveness and their semantic, structural signs that form functional semantic pole of each of these categories. The predicate together with the subject creates the central place in a complex of predicative fields.The main categories of predicativeness such as modality, temporality, and personality being expressed by a predicate form show the attitude of action and the utterance to reality from the position of the speaker.In the Kazakh language there are many means of expression of the predicate, they form the core and periphery, which are analyzed in the article. Posessiveness expresses the relation of objects and the phenomenon of the reality belonging to a person or objects and phenomena based on social factors or expresses specific links between objects and phenomena. Each nation has originality in the development of reality and it is reflected in the language in its own way. One of the features of the Kazakh language is Turkish izafat as the expression of possessiveness. Semantic and structural features of this category are considered in the article.
Keywords: functionality; predicativeness; possessiveness; functional-semantic field; core and periphery